Dermatoscopic features of lichen nitidus. Issue 6 (26th June 2018) - Jakhar, Deepak; Grover, Chander; Kaur, Ishmeet; Sharma, Sonal
Abstract: Dermatoscopy is a noninvasive, painless, and easily repeatable technique that reveals interesting and characteristic features associated with various cutaneous conditions. Lichen nitidus is a rare dermatosis of childhood. We describe the dermatoscopic features in 8 cases of lichen nitidus, which can aid noninvasive diagnosis. The report serves to emphasize the need for examining these lesions using both polarized and nonpolarized modes.